Qualidade da assistência à criança hospitalizada sob a ótica do acompanhante - Ylana Karine Fonseca de Medeiros; Deborah Dinorah de Sá Mororó; Juliana Teixeira Jales Menescal Pinto; Nadja de Sá Pinto Dantas Rocha; Gleiciane da Silva Fonseca (Universidade Federal do Ceará, 2017)
Objective: to assess the companion's satisfaction with the quality of care provided to the hospitalized child. Methods: this is an evaluative study, carried out in a pediatric hospitalization unit of a University Hospital. Seventy companions of hospitalized children met the inclusion criteria and answered to the data collection instrument, composed of a form with socioeconomic information and another adapted to assess user satisfaction from the National Health Services Evaluation Program. Results: 45.7% reported some delay in care during the child's hospitalization. There was satisfaction with the communication of information about the patient (88.6%), visit time (75.7%), cleaning of the environments (75.7%), but 65.7% did not know where to make complaints or suggestions and 44.3% did not know the name of the professional who would see their child. Conclusion: in general, companions' satisfaction regarding the quality of care for hospitalized children was evidenced, and opportunities for improvement regarding users' rights were highlighted.